2002
DOI: 10.1007/bf03027025
|View full text |Cite
|
Sign up to set email alerts
|

Densification and compressive strength ofin-situ processed Ti/TiB composites by powder metallurgy

Abstract: In the present study, the densification of Ti/TiB composites, the growth behavior of in-situ formed TiB reinforcement, the effects of processing variables -such as reactant powder (TiB 2 , B 4 C), sintering temperature and time -on the microstructures and the mechanical properties of in-situ processed Ti/TiB composites have been investigated. Mixtures of TiB 2 or B 4 C powder with pure titanium powder were compacted and presintered at 700 o C for 1 hr followed by sintering at 900, 1000, 1100, 1200, and 1300 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
1
8
1
1
Order By: Relevance
“…This indicates the occurrence of a chemical reaction between CP-Ti and TiB2 powder during the SLM process, leading to the formation of Ti-TiB composite. This is similar to other studies, in which a chemical reaction between Ti and TiB2 during processing has been reported [13,15,16] . Fig.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates the occurrence of a chemical reaction between CP-Ti and TiB2 powder during the SLM process, leading to the formation of Ti-TiB composite. This is similar to other studies, in which a chemical reaction between Ti and TiB2 during processing has been reported [13,15,16] . Fig.…”
Section: Methodssupporting
confidence: 92%
“…Generally, conventional technologies such as casting [15] and powder metallurgy [16] are applied for in situ producing of Tibased composites but these methods are usually time-, energy-and material-consuming and it is not easy to fabricate complex-shape parts, which are highly needed in many fields specially biomedical industry. Emerging advanced technologies such as additive manufacturing techniques can not only produce 3D-shape components of high quality and complex features but also be capable of reducing production time as well as increasing primary material usage [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used different compounds in order to reinforce Ti and these include TiN [12], TiC [13], SiC [14], B 4 C [15] and TiB [16]. As shown in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was obtained through the addition of 15 wt.% of Mo into Ti. The composite produced by SPS showed a very attractive combination of strength and ductility (1.5-2 GPa and~22%, respectively) ( Figure 3a) at room temperature, which is superior to most of the β-rich alloys in the heat-strengthened condition [22] or metal-matrix composites with the hcp α-Ti matrix [4,23,24]. The observed increase in ductility is obviously associated with a greater number of slip systems in the bcc lattice in comparison with that of the hcp one [25].…”
Section: Discussionmentioning
confidence: 99%